(untitled) (CIPEEX, 2025)
Infection by Sars-Cov-2 occurs through inhalation or direct contact with contaminated droplets, with high infection potential that generated lethality levels never seen before in such a short period of time. Although it has symptoms similar to Influenza, there is a greater potential for complications such as encephalitis, severe hypoxemia, encephalopathies, and neuronal degeneration, which are common in cases of Stroke (ischemic or hemorrhagic). From this perspective, studies show that the Sars-Cov-2 virus has neuroinvasive properties and that the probability of death from stroke after Sars-Cov-2 infection increases up to five times compared to non-infected individuals. Thus, this research aims to describe the relationship between stroke and COVID-19 infection, considering the age group of 50 to 85 years in Anápolis, and to support health care services. This is a cross-sectional, descriptive, and quantitative study. A total of 200 medical records were collected between 2020 and 2021, of patients aged 50 to 85 years with positive PCR and symptoms of COVID-19, both at outpatient and inpatient levels at the Evangelical Hospital of Goiás. It was observed that out of 200 patients, 120 had previous comorbidities; patients with a history of prior stroke developed more severe complications; the main complications were pulmonary; and at the chosen hospital, there were no confirmed cases of post-COVID stroke in the studied age group.